Dexmedetomidine Induced Polyuria in the Intensive Care Unit. (22nd February 2021) - Uddin, Mohammed M.; Sebastian, Joseph; Usama, Muhammad; Raziq, Fazal I.; Saydain, Ghulam; Rossi, Noreen F.
Abstract : Dexmedetomidine is an α 2-adrenergic used as an adjunct therapy for sedation in the intensive care unit. While it is known to cause polyuria exclusively in perioperative conditions, not many cases are known in the intensive care unit, thus making the diagnosis challenging. We present the case of a 61-year-old male who had developed polyuria secondary to central diabetes insipidus after receiving dexmedetomidine intravenous infusion in the medical ICU. Increased awareness of this uncommon side effect of dexmedetomidine will help clinicians recognize and address it early.